Development of a Learning Device Information System for Kindergartens - Rohita Rohita; Nila Fitria; Dody Haryadi; Radhiya Bustan (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to develop a learning device information system, abbreviated as SIPP, as a way of compiling multiple learning devices that include weekly learning implementation plans (RPPM), daily learning implementation plans (RPPH), and learning assessments. The system was built using unified modelling language (UML). After the system was tested at 15 kindergarten institutions in South Jakarta and Tangerang City, the data collected showed that out of 15 teachers, 88% stated that SIPP was very helpful in compiling RPPM and RPPH, as well as conducting assessments and filling out report cards. Additionally, of 15 school principals, 80% strongly agreed that SIPP can help conduct classroom management and monitor and evaluate teachers’ teaching preparations. Based on these findings, it can be concluded that the learning device information system developed can help teachers prepare lesson plans in kindergarten, as well as help school principals monitor teacher performance related to the preparation of lesson plans.